Clinker Efficiency in the Treatment of Low-Plasticity Clay - Avcı, Eyübhan; Mollamahmutoglu, Murat (Asce-Amer Soc Civil Engineers, 2018)
This paper presented some geotechnical characteristics of low plasticity clay (LPC) treated with clinker in comparison with those of ordinary portland cement (OPC) treated LPC. The chosen percentages of both additives were 10, 12, and 14% for the stabilization of LPC. While the liquid limits of clinker and OPC treated LPC decreased, their plastic limits increased. The liquid limit (LL) and the plastic limit (PL) of clinker treated LPC were found to be lower than those of OPC treated LPC. The optimum moisture content (OMC) and maximum dry density (MDD) of LPC were increased by both clinker and OPC treatment. In addition, the OMC values of clinker treated LPC were higher than those of OPC treated LPC. However, the MDD values of clinker and OPC treated LPC were almost the same. The shear strength of LPC was also increased with the clinker and OPC treatments under both the wet-cured and air-dried conditions. The compressibility and swell characteristics of LPC were considerably reduced by both clinker and OPC treatments. Nevertheless, the swell and compressibility of clinker treated LPC were lower than those of OPC treated LPC. It was found that the clinker was more effective than that of OPC in the treatment of LPC. (c) 2018 American Society of Civil Engineers.
Keywords: Clinker; Ordinary portland cement; Clay; Strength; Compressibility; Swelling